PENINGKATAN KEMAMPUAN BELAJAR ILMU PENGETAHUAN ALAM DENGAN METODE EKSPERIMEN - Niryandi Niryandi (STKIP ROKANIA, 2017)
The experiment method can improve ability to learning Natural Science for students of class IV SD Negeri 008 Rambah Samo, Kecamatan Rambah Samo, Kabupaten Rokan Hulu”. This method is very suitable applied in SD Negeri 008 Rambah Samo, because the students trained to find aswer, express opinions, and summed up the problem. Provent in students leaning able to make conclusion based on experimental result. And this method able to improve students learning outcomes result of students learning so that value is above the minimum mastery criteria from cycles I to cycle II is from 66 from pre-research to 79 in cycle I and 88 in cycle II